Preferences in the use of communication technology: the influence of the gender dimension among higher education students - Morais, Nídia Salomé (2016)
This paper presents some of the findings of a nationwide study, which was designed for understanding aspects related to the use of Communication Technology (CT) among higher education students in Portugal. This descriptive and exploratory study essentially focused on gender issues, particularly on how they influence the students’ perception regarding the use of CT. The data collection method selected was online survey. The findings reveal, among other results, students’ preferences regarding CT use and gender differences in that context.